A nationwide analysis of clinical trial participation for common hepato-pancreato-biliary malignancies demonstrates survival advantages for subsets of trial patients but disparities in and infrequency of enrollment. Issue 8 (August 2022) - Elshami, Mohamedraed; Hue, Jonathan J.; Hoehn, Richard S.; Rothermel, Luke D.; Bajor, David; Mohamed, Amr; Selfridge, Jennifer E.; Chavin, Kenneth D.; Ammori, John B.; Hardacre, Jeffrey M.; Winter, Jordan M.; Ocuin, Lee M.
Abstract: Background: We describe factors associated with trial enrollment for patients with hepato-pancreato-biliary (HPB) malignancies. We analyzed the association and effect of trial enrollment on overall survival (OS). Methods: The National Cancer Database (2004–2017) was queried for common HPB malignancies (pancreatic adenocarcinoma [PDAC] & neuroendocrine tumors, hepatocellular carcinoma [HCC], biliary tract cancers [BTC]). Multivariable logistic regression was used to identify factors associated with trial enrollment. OS was analyzed by multivariable Cox regression. Inverse-probability-weighted Cox regression was utilized to determine the effect of trial enrollment on OS. Results: A total of 1573 (0.3%) of 511, 639 patients were enrolled in trials; pancreatic malignancy: 1214 (0.4%); HCC: 217 (0.14%); BTC: 106 (0.15%). HCC and BTC were associated with lower likelihood of enrollment compared with pancreatic malignancy. Black and Hispanic patients were less likely to be enrolled compared to White patients. Treatment at academic facilities and metastatic disease were associated with higher likelihood of enrollment. Enrollment was associated with higher OS for PDAC, metastatic HCC, and metastatic BTC. Trial enrollment exhibited an OS advantage for PDAC and metastatic HCC. Conclusion: Nationally, fewer than 1% of patients with HPB malignancies were enrolled in clinical trials. There are racial, sociodemographic, and facility-based disparities in trial enrollment.